Respuesta :

snog

Answer:

[tex]16[/tex]

Step-by-step explanation:

Substituting [tex]a=2[/tex] and [tex]b=3[/tex] into [tex](a^{b}+b^{a})-1[/tex] gives us:

[tex](a^{b}+b^{a})-1[/tex]

[tex]=(2^{3} +3^{2})-1[/tex] (Substitute given values into expression)

[tex]=(8+9)-1[/tex] (Evaluate exponents)

[tex]=17-1[/tex] (Evaluate expression in parentheses)

[tex]=16[/tex] (Simplify)

Hope this helps!

Answer:

16

Step-by-step explanation:

Given

([tex]a^{b}[/tex] + [tex]b^{a}[/tex] ) - 1 ← substitute a = 2, b = 3

= (2³ + 3²) - 1

= (8 + 9) - 1

= 17 - 1

= 16

ACCESS MORE